Ciguatera Fish Poisoning: Treatment, Prevention and Management - Andrew Reich; Ray Granade; Sharon Watkins; Richard Weisman; Ram Ayyar; Lorraine Backer; Marie-Yasmine Bottein; Robert Dickey; Kathleen Schrank; Paul Bienfang; Mercedes Fernandez; Lora E. Fleming; et al. (Marine Drugs, 2008)
Ciguatera Fish Poisoning (CFP) is the most frequently reported seafood-toxin illness in the world, and it causes substantial physical and functional impact. It produces a myriad of gastrointestinal, neurologic and/or cardiovascular symptoms which last days to weeks, or even months. Although there are reports of symptom amelioration with some interventions (e.g. IV mannitol), the appropriate treatment for CFP remains unclear to many physicians. We review the literature on the treatments for CFP, including randomized controlled studies and anecdotal reports. The article is intended to clarify treatment options, and provide information about management and prevention of CFP, for emergency room physicians, poison control information providers, other health care providers, and patients.